0262 An Exploratory Examination of the Relationship Between Negative Affect, Stress and Emotional Reactivity, Mindfulness, and Sleep Incompatible Behaviors. (27th May 2020) - Nagy, S; Pickett, S M; Sosa, J; Garcell, A
Abstract: Introduction: Stress has been identified as a barrier to engaging in positive health behaviors. Sleep interventions, including sleep hygiene recommendations, highlight stress management as an important treatment component. However, the relationship between negative emotion, stress management or emotion regulation, and positive sleep behaviors has largely been unexamined. Therefore, the current study, through secondary analyses, examined the relationships between negative affect, stress and emotional reactivity and sleep incompatible behaviors. Lastly, the indirect effect that dispositional mindfulness, as a possible self-regulatory mechanism, may have on the relationship was also examined. It was hypothesized that greater levels of stress, emotional reactivity, and negative arousal along with lower levels of dispositional mindfulness would predict higher engagement in sleep incompatible behaviors. Methods: Participants (n=308) identified mostly as female (55.8%) and White/Caucasian (83.2%) and with an average age of 36.76 (SD = 12.20). Participants completed the Perceived Stress and Reactivity Scale (PSRS), the Positive and Negative Affect Scale (PANAS), the Sleep Behaviors Self-Rating Scale, and the Five Facet Mindfulness Questionnaire (FFMQ). A multiple regression analysis was conducted using the relevant subscales from the PSRS, PANAS, and FFMQ to predict the occurrence of behaviors incompatible with healthy sleep. Results: The hypothesis was partially supported. Results indicated that the model significantly predicted sleep incompatible behavior (R 2 = .108, F(9, 299) = 4.042, p < .001), with only negative affect (β= .163, t(299) = 2.555, p = .011) and nonreactivity (β= -.219, t(299) = -2.484, p = .014) remaining significant when all variables were entered in the model. Conclusion: The findings demonstrate that negative affect and reactivity are significant predictors of engagement in poor sleep hygiene practices. They also suggest that certain facets of dispositional mindfulness has an indirect relationship with sleep incompatible behaviors. The results may contribute to the development of sleep health interventions and highlight the need for future research. Support: N/A